Justice in education and recognitive justice - Hanhela, Teemu Eino Petteri (Studier i Pædagogisk Filosofi, 2018)
This paper focuses on a topical issue - the idea of ‘justice in education’ – developed by Krassimir Stojanov, among other recent educational justice theorists. Justice in education has to ask ‘educational questions about education’, which means that educational justice theory should be capable of dealing with educational practices, and constellations that are asymmetrical interaction orders. This requires, from the perspective of a child, criteria to distinguish between justified and unjustified educative demands towards responsibility and autonomy. This paper analyses forms of recognition as a legitimate summons that enables the individual’s autonomy. It also analyses the illegitimate demands that emerge from Stojanov’s innovative idea to combine the forms of misrecognition with the concepts of epistemic injustice. The second chapter of this paper introduces the challenges related to the recognitive justice as justice in education. The examination of Dietrich Benner’s recent critique of recognition theory illuminates these challenges in two ways: first, it is shown that there can be something negatively experienced, but the result of productive disruptions that the educator need to produce, which are out of the scope of recognition theory. Second, the recognitive justice paradigm ignores elementary pedagogical conditions and requirements, ‘the pedagogical knowledge’ and its methods, and is therefore unable to fully grasp the legitimate educational authority. This paper concludes with a synthesis that finds the crucial elements from the recognition theory to justice in education and critically assessing Benner’s claims. Overall, the paper offers potential for further development in justice in education.